MURIN: Multimodal Retinal Imaging and Navigated-laser-delivery for dynamic and longitudinal tracking of photodamage in murine models - Rico-Jimenez, Jose J.; Jovanovic, Joel; Nolen, Stephanie L.; Malone, Joseph D.; Rao, Gopikrishna M.; Levine, Edward M.; Tao, Yuankai K. (Frontiers in Ophthalmology, 2023)
Laser-induced photodamage is a robust method for investigating retinal pathologies in small animals. However, aiming of the photocoagulation laser is often limited by manual alignment and lacks real-time feedback on lesion location and severity. Here, we demonstrate a multimodality OCT and SLO ophthalmic imaging system with an image-guided scanning laser lesioning module optimized for the murine retina. The proposed system enables targeting of focal and extended area lesions under OCT guidance to benefit visualization of photodamage response and the precision and repeatability of laser lesion models of retinal injury.